REPRESENTASI BULLYING DALAM FILM JAROS INDZAR KARYA KHALID FAHAD (KAJIAN SEMIOTIKA CHARLES SANDERS PEIRCE) - Dzifriya Qatrun Nada; Akmaliyah Akmaliyah; Rohanda Rohanda (Universitas Islam Negeri Sumatera Utara Medan, 2026)
The school environment should ideally be a safe space for children to learn and develop social relationships. However, in reality, schools often become sites where bullying occurs, as represented in the short film Jaros Indzar by Khalid Fahad. This study aims to analyze the representation of bullying in the short film Jaros Indzar using Charles Sanders Peirce’s semiotic approach. The research employs a descriptive qualitative method with Peircean semiotic analysis, focusing on the triadic relationship between sign, object, and interpretant. The findings indicate that Jaros Indzar represents various forms of bullying, including non-verbal, verbal, and psychological bullying. At the level of sign, five scenes were identified as representing non-verbal bullying, such as pushing, locking someone in, talking behind someone’s back, taking belongings, and making offensive gestures. At the level of object, five scenes represent verbal bullying in the form of insulting, threatening, blaming, cornering, and mocking. Meanwhile, at the level of interpretant, six scenes represent psychological bullying, including cynical stares, mocking laughter, sarcastic smiles, intimidation, and acts of instilling fear.This study demonstrates that Jaros Indzar presents a complex representation of bullying through visual and narrative signs, making the film a reflective and educational medium for understanding the impacts of bullying in the school environment.